ASPEK ADMINISTRASI DAN MANAJEMEN PERBATASAN NEGARA - Anak Agung Banyu Perwita (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2009)
The management of development in our border issues, which to date has not been optimal, is a crucial issue in Indonesia today. This internal problem and the possibility of neighboring countries claiming part of our national territory have increasingly turned this issue into a priority for the Indonesian government. This article discusses our limited capacity to manage and protect its boundaries which will have real impacts to both internally and externally. This article argues thatthe complicated character of the national border issue, which is related to various types of threat, the wider field of national security, limited resources and the perception of threats, requires a more comprehensive policy framework. Internally, the effective management of national territorial boundaries will not only strengthen nation-state building but also contribute to the creation of regional security. This can be achieved by establishing cooperation with the relevant neighboring states. But, of course, we must also be able to take cognizance of various other dimensions, such as the economic, social, legal and diplomatic fields in managing our national borders.